Persistence, switch rates, drug consumption and costs of biological treatment of rheumatoid arthritis: an observational study in Italy - Degli Esposti L; Favalli EG; Sangiorgi D; Di Turi R; Farina G; Gambera M; Ravasio R (Dove Medical Press, 2016)
Luca Degli Esposti,1 Ennio Giulio Favalli,2 Diego Sangiorgi,1 Roberta Di Turi,3 Giuseppina Farina,4 Marco Gambera,5 Roberto Ravasio,6 1CliCon S.r.l. – Health, Economics & Outcomes Research, Ravenna, 2Department of Rheumatology, Istituto Ortopedico Gaetano Pini, Milan, 3Local Pharmaceutical and Supplementary Assistance Unit, Roma Local Health Authority D, Rome, 4Internal Management Control Unit – Pharmaceutical Spending Control Sector, Caserta Local Health Authority, Caserta, 5Local Pharmaceutical Service, Bergamo Local Health Authority, Bergamo, 6Health Publishing & Services Srl, Milan, Italy Objectives: The aim of this analysis was to provide an estimate of drug utilization indicators (persistence, switch rate and drug consumption) on biologics and the corresponding costs (drugs, admissions and specialist care) incurred by the Italian National Health Service in the management of adult patients with rheumatoid arthritis (RA).Methods: We conducted an observational retrospective cohort analysis using the administrative databases of three local health units. We considered all patients aged ≥18 years with a diagnosis of RA and at least one biologic drug prescription between January 2010 and December 2012 (recruitment period). Persistence was defined as maintenance over the last 3 months of the follow-up period of the same biological therapy administered at the index date. A switch was defined as the presence of a biological therapy other than that administered at the index date during the last 3 months of the follow-up period. Hospital admissions (with a diagnosis of RA or other RA-related diagnoses), specialist outpatient services, instrumental diagnostics and pharmaceutical consumption were assessed.Results: The drug utilization analysis took into account only biologics with at least 90 patients on treatment at baseline (adalimumab n=144, etanercept n=236 and infliximab n=94). In each year, etanercept showed better persistence with initial treatment than adalimumab or infliximab. Etanercept was characterized by the lowest number of patients increasing the initial drug consumption (2.6%) and by the highest number of patients reducing the initial drug consumption (10.5%). The mean cost of treatment for a patient persisting with the initial treatment was €12,388 (€14,182 for adalimumab, €12,103 for etanercept and €11,002 for infliximab). The treatment costs for patients switching from initial treatment during the first year of follow-up were higher than for patients who did not switch (€12,710 vs. €11,332).Conclusion: Persistence, switch rate and drug consumption seem to directly influence treatment costs. In subjects not persisting with initial treatment, other health care costs were approximately three times higher than for persistent patients. This difference could suggest a positive effect on the quality of life for persistent patients. Etanercept showed the highest persistence with treatment. Keywords: rheumatoid arthritis, biologic drugs, real-life clinical conditions